Peran Pendidikan Karakter Untuk Membentuk Karakteristik Peserta Didik Di Abad 21 - Luthfi, Tiara; Puspita Sari, Rissa; Sallsabila, Irma; Wahyudin, Dede; Caturiasari, Jennyta (FKIP, PGSD, Universitas Slamet Riyadi, 2025)
In the 21st century, the rapid development of technology has penetrated the world of education. Learners are required to adapt to the digital world. In positive terms, technology makes it easier for students to access learning. But in fact, technology is like a double-edged knife. Technology can have a negative impact on students, one of which is the fading of the morals and ethics of the nation's children. Therefore, to encourage quality and moral education, the government held a Strengthening Character Education (PPK) program. This research uses a literature study method (library research). This article is reviewed with the aim of realizing the importance of implementing character education to shape the characteristics of students in the 21st century to become advanced, superior, and intelligent individuals. The research results of this article show that character education has an important role in creating a quality young generation.